168k views
1 vote
Anyone happen to know this? Thanks.

Anyone happen to know this? Thanks.-example-1
User Lhagemann
by
5.3k points

1 Answer

7 votes

Answer:

A

Explanation:

given y = f(x) then y = f(x + c) represents a horizontal translation

• If c > 0 then shift to the left of c units

• If c < 0 then shift to the right of c units

given y = f(x) then f(x) + c represents a vertical translation

• If c > 0 then shift up by c units

• If c < 0 then shift down by c units

here f(x) = | x | thus a shift of 4 units right is f(x) = | x - 4 |

and a shift of 6 units up gives

f(x) = | x - 4 | + 6 → A

User Striatum
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.